Intravenous ferric carboxymaltose for the treatment of iron deﬁciency anemia - Friedrisch,João Ricardo (2015)
ABSTRACT Nutritional iron deﬁciency anemia is the most common deﬁciency disorder, affecting more than two billion people worldwide. Oral iron supplementation is usually the ﬁrst choice for the treatment of iron deﬁciency anemia, but in many conditions, oral iron is less than ideal mainly because of gastrointestinal adverse events and the long course needed to treat the disease and replenish body iron stores. Intravenous iron compounds consist of an iron oxyhydroxide core, which is surrounded by a carbohydrate shell made of polymers such as dextran, sucrose or gluconate. The ﬁrst iron product for intravenous use was the high molecular weight iron dextran. However, dextran-containing intravenous iron preparations are associated with an elevated risk of anaphylactic reactions, which made physicians reluctant to use intravenous iron for the treatment of iron deﬁciency anemia over many years. Intravenous ferric carboxymaltose is a stable complex with the advantage of being non- dextran-containing and a very low immunogenic potential and therefore not predisposed to anaphylactic reactions. Its properties permit the administration of large doses (15 mg/kg; maximum of 1000 mg/infusion) in a single and rapid session (15-minute infusion) without the requirement of a test dose. The purpose of this review is to discuss some pertinent issues in relation to the history, pharmacology, administration, efﬁcacy, and safety proﬁle of ferric carboxymaltose in the treatment of patients with iron deﬁciency anemia.